2022
DOI: 10.3346/jkms.2022.37.e39
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Thyroiditis After Receiving the mRNA COVID-19 Vaccine (Moderna): The First Case Report and Literature Review in Korea

Abstract: Subacute thyroiditis (SAT) is a painful thyroiditis that often requires steroid therapy. Here, we report the first case of severe SAT in a patient who received the first dose of mRNA coronavirus disease 2019 (COVID-19) vaccination. A 34-year-old man without a viral prodrome felt a lump when swallowing 5 days after his first dose of mRNA-1273 (Moderna) vaccination. Ten days after vaccination, the patient visited the hospital and was advised to rest and take nonsteroidal anti-inflammatory drugs. He revisited the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Subacute thyroiditis, a self-limited disease is one of the most common causes of anterior cervical pain and is associated with thyroid dysfunction.It is an uncommon disease that has a high prevalence among middle-aged females and constitutes 5% of thyroid disease.Viral Infection is the most likely cause [ 10 ].Many viruses like enterovirus (being the most common), influenza virus,coxsackievirus,mumps,measles, and other viruses predispose to upper respiratory tract infection as one of the secondary causes [ [11] , [12] , [13] , [14] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subacute thyroiditis, a self-limited disease is one of the most common causes of anterior cervical pain and is associated with thyroid dysfunction.It is an uncommon disease that has a high prevalence among middle-aged females and constitutes 5% of thyroid disease.Viral Infection is the most likely cause [ 10 ].Many viruses like enterovirus (being the most common), influenza virus,coxsackievirus,mumps,measles, and other viruses predispose to upper respiratory tract infection as one of the secondary causes [ [11] , [12] , [13] , [14] ].…”
Section: Discussionmentioning
confidence: 99%
“…Subacute thyroiditis is genetically influenced and is associated with HLA B35 and the susceptibility is more when accompanied by viral infection [ 12 ]. Genetically susceptible individuals carry human leukocyte antigen haplotype.Viral antigen binds to HLA B35 molecules on the macrophages activating cytotoxic T lymphocytes which damage thyroid follicular cells [ 13 ].On palpation, the thyroid is painful,tender, and enlarged.Ace 2 and Transmembrane protease serine 2 receptors which are expressed in different tissues are involved in the pathogenesis of covid 19. Thyroid Follicular cells which express ACE2 make it more susceptible to injury due to Covid 19 [ 16 ].It could be either a direct or immune-mediated injury of the thyroid gland where thyroid hormones activate signal pathways that control the transcription of genes involved in anti-apoptotic,angiogenetic, and ultimately cell proliferation, by binding to integrin receptors [ 16 ].The severe form of Covid 19 is interlinked with several cytokines,chemokines, and several viral proteins,which may aggravate the underlying subacute thyroiditis with increased IL-6 and TNF alpha levels [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another clinical case study, three patients with no previous history of thyroid disease presented with thyrotoxicosis 10–20 days after receiving the Pfizer, Bio-NTech, or Moderna mRNA vaccine [ 32 ]. A literature review conducted by Jhon et al revealed that out of the 22 SAT cases reported, 13 patients required steroid therapy and the remaining cases subsided with supportive treatment [ 33 ].…”
Section: Covid-19 Induced Thyrotoxicosismentioning
confidence: 99%
“…As such, cases of autoimmune flares could be potentially seen as mere side effects from inflammatory cytokine bursts of IFN that would transiently resolve overtime. This could potentially explain why patients who developed hyperthyroidism or hypothyroidism post-vaccination did not experience severe complications and experienced symptomatic relief with supportive care or steroids [ 33 ]. Regardless, it is still widely unknown whether the onset of autoimmune thyroid disorders is a causal association with SARS-CoV-2 vaccination or a mere coincidence.…”
Section: Covid-19 Induced Thyrotoxicosismentioning
confidence: 99%
“… 2 3 4 5 6 7 8 9 10 11 12 13 In Korea, while a few cases of SAT after receiving a COVID-19 mRNA vaccine were reported, there has been no report of SAT following COVID-19. 14 15 Although Graves’ disease (GD) is the most common cause of thyrotoxicosis in general, accounting for 60–80% of all thyrotoxicosis cases, thyrotoxicosis related to COVID-19 is mainly due to SAT, with only two cases of GD after COVID-19 reported. 16 Moreover, the simultaneous occurrence of SAT and GD is a rare phenomenon and has not been reported in association with COVID-19 in the literature yet.…”
Section: Introductionmentioning
confidence: 99%